2000
DOI: 10.1046/j.1464-410x.2000.00322.x
|View full text |Cite
|
Sign up to set email alerts
|

Microvessel density in prostatic hyperplasia

Abstract: Objectives To examine the prostates from patients with haematuria associated with benign prostatic hyperplasia (BPH) to determine their microvascular anatomy and thus assess histopathological differences in patients with significant haematuria. Patients and methods Prospectively, 11 patients with BPH and haematuria (mean age 70 years) and 19 control patients with BPH alone (mean age 72 years) were identified. Neither group had received hormone manipulation or had been catheterized. The sub‐urothelial compartme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
33
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 18 publications
1
33
0
2
Order By: Relevance
“…Thus, prostatic blood flow is increased in patients with BPH due to the increased metabolic demands of a larger gland. It has also been found that microvessel density of suburothelial compartments of the prostatic urethra was greater in patients with hematuria related to BPH [9]. Recent studies have demonstrated that finasteride reduces the suburothelial vascularity of the prostatic urethra in humans and the prostatic blood flow in rats, confirming the role of androgens in the regulation of prostatic blood flow and angiogenesis [10,11].…”
Section: Discussionmentioning
confidence: 83%
“…Thus, prostatic blood flow is increased in patients with BPH due to the increased metabolic demands of a larger gland. It has also been found that microvessel density of suburothelial compartments of the prostatic urethra was greater in patients with hematuria related to BPH [9]. Recent studies have demonstrated that finasteride reduces the suburothelial vascularity of the prostatic urethra in humans and the prostatic blood flow in rats, confirming the role of androgens in the regulation of prostatic blood flow and angiogenesis [10,11].…”
Section: Discussionmentioning
confidence: 83%
“…Increased vascularity in the prostatic suburothelium in haematuria patients who underwent TURP has been shown. 8 We suspect that, in the patients with vascular prostatic regrowth under discussion here, the prostatic regrowth would show a similar histological increase in microvessel density compared to non-bleeding patients with an equivalent degree of BPH. It would be interesting to compare the histology of prostatic suburothelium from the initial TURP to the bleeding growth to see if there was a predisposition to increased microvascularity or if the TURP altered the histological character of the hyperplastic tissue.…”
Section: Discussionmentioning
confidence: 83%
“…Patients with clinical BPH and recurrent gross hematuria have a significantly higher suburethral prostatic microvessel density than patients with BPH alone [9]. BPH associated hematuria is probably related to the increased vascularity of the prostate [6,10].…”
Section: Discussionmentioning
confidence: 96%
“…Treatment options for prostatic bleeding include tamponade of the prostate with a urethral catheter, endoscopic resection and fulguration of the prostate, hormonal ablation, use of antifibrinolytic agents, or careful observation with limiting of physical activity. MVD is a histological measurement of angiogenesis and thus a surrogate marker of bleeding, as the prostates of men with BPH and haematuria have a significantly higher MVD in the suburethral portion than prostates of men with BPH alone [9]. Prostatic microvessel density is a histological and clinical indicator of angiogenesis in patients with BPH.…”
Section: Discussionmentioning
confidence: 99%